The Gender Gap Among EduTubers and the Factors Significantly Influencing It - Daniel Pattier (Springer, 2021)
An increased use of YouTube in education has resulted in the emergence of a large number of audiovisual educational content creators known as EduTubers. Our research considers gender as a relevant variable within this group by analysing the 204 most successful channels in Spain so as to identify the existence of models and reference points throughout the area of informal education. The study methodology is based on a qualitative analysis instrument that provides descriptive statistics and contingency tables. The results provide original evidence on the topic. We reflect on the possible existence of a gender gap among EduTubers, concluding that there is actually one. After identifying the significant factors regarding to this inequality, they were grouped together into four categories: media exposure level; women's participation in the educational stages that are most in demand on YouTube; elements and factors determining the success of videos; and time spent on the channel as a content creator. A suggestion is made of possible steps to reduce this gender gap through emotional support and training aimed at women who wish to become EduTubers, as well as via social change that facilitates the presence of women as influential figures in informal education.